Numerical investigations of impeller–diffuser interactions in a transonic centrifugal compressor stage using nonlinear harmonic method. (December 2014) - Liu, Baojie; Zhang, Bo; Liu, Yangwei
Numerical investigations have been conducted on a transonic centrifugal compressor stage with a vaned diffuser. Due to the high loading and small radial gap between the impeller and diffuser, the unsteady impeller–diffuser interactions can be very large compared with axial compressors, and this has a significant impact on the time-averaged performance of a centrifugal compressor stage. Steady, unsteady and NonLinear Harmonic (NLH) simulations have been carried out to study the interactions in a transonic centrifugal compressor. Comparisons have been made against the overall performance and flow details. The distribution of deterministic correlations are extracted and compared to show the effect of unsteadiness due to impeller–diffuser interactions. All of these analyses show that the NLH method gains more accuracy compared with the steady-state mixing plane simulation and saves CPU time compared with an unsteady time-accurate computation. NLH and unsteady methods are in good agreement in overall performance predictions compared with the steady-state mixing plane method while small differences still exist in flow details. In general, the NLH method obtains good accuracy in terms of both deterministic stress and enthalpy correlations which are sufficiently accurate to be directly used in model development in the average-passage equation system instead of the more time-consuming unsteady simulation.